If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11g-12=8g
We move all terms to the left:
11g-12-(8g)=0
We add all the numbers together, and all the variables
3g-12=0
We move all terms containing g to the left, all other terms to the right
3g=12
g=12/3
g=4
| 21/x=0.5 | | 13x-7=2x+13 | | 7b+750=823.50 | | 12/9=q/24 | | -2u+20=2u+6(u-20) | | 4y-3^2=12 | | 5x-29=63 | | 7(3p+4)+1=7p+15 | | |x-33|=5 | | 25=-3b-8 | | 44=56+2y | | 3(1)+5y=8 | | 4x-5=2(2x-10)-3 | | -15b+2+5b=-19 | | −13x=12 | | x+55+50=80 | | F(-5)=14x^2+19 | | 3x-3=9+1x | | -9-9|-2x+7|=-108 | | 11=-3x-13 | | 8x−2(3x+5)=6x | | 9(x-4)+20=9x-16 | | 30+2x=8x-6 | | 120+130+x=180 | | b+5/10=3 | | 24/f=15/36 | | 82=3x+15 | | (n)/(1.2)=-36 | | 6x-20=4(½x+5) | | -3n-8=`10 | | 3(x-7)+14=2x-3 | | 3x+2+4.5=-4+10x |